Alterações morfofuncionais cardíacas induzidas pelo veneno da Crotalus durissus casavella- serpente de alta prevalência no Estado da Bahia. - Simões, Letícia Oliveira (2019)
The venom of Crotalus durissus cascavella (CDC) may be a source of bioprospecting for new therapeutic agents with cardiovascular action, however, the biological effects induced in cardiac tissue are not fully understood. AIM: To investigate the influence of CDC venom on the cardiac activity of rats and their possible mechanisms of action involved. METHODS: Atrium isolated from wistar male and spontaneously hypertensive rats (SHR) (12-16 weeks) were maintained in organ bath with Krebs-bicarbonate solution, and after a stabilization period, CDC (0.1-30 ìg/mL) was added cumulatively to the organ bath. Changes on the contractility of cardiomyocytes were evaluated by means of the cardiomyocyte length alteration technique, using a border detection system. Rat cardiomyocytes of the H9c2 strain were used to evaluate the cytotoxicity of the compound on mammalian cells at different concentrations (0.37-30 ìg/mL). For quantification of the total creatine kinase (CK) enzyme activity, krebs samples were collected before and after the addition of the venom in the organ bath and quantitated using a commercially available assay kit. Morphological and ultrasound analyzes of the cardiomyocyte were performed to investigate some type of cardiac lesion. The influences of CDC on cardiac electrical activity were investigated through Langendorff's system. The mechanism of action of cardiac effect of CDC was investigated on atrial tissue in the presence of Epinephrine (10 ìM), Propranolol (10 ìM), L-NAME (100 ìM); PTIO (100 ìM); ODQ (10 ìM) and KT5823 (1ìM). Evaluation of the effects of CDC on the hemodynamics of non-anesthetized rats and ECG were performed in the set of in vivo experiments. The tests carried out were approved by CEUA (CEUA-ICS / UFBA n ° 072/2014). Statistical analyzes were performed using Student's t-test or one-way ANOVA followed by Bonferroni test, when appropriate using GraphPadPrism 6.0® (USA). RESULTS: CDC induced a negative inotropic effect on isolated rat atrium, as well as reduced contractility on isolated cardiomyocytes. CDC at concentrations of 7.5, 15 and 30 ìg/mL did not induce a significant change in cardiomyocyte cell proliferation. Treatment of the atria of rats with CDC (30 ìg/mL) did not significantly alter the levels of CK-Total and CK-MB in physiological solution containing atrial tissue. In addition, the CDC venom did not induce important morphological or ultrastructural changes as well as cardiac electrogenesis evaluated through the Langendorff system. CDC was not able to induce negative inotropic effect in isolated atrium in the presence of L-NAME, PTIO, ODQ and KT5823. In non-anesthetized CDC rats induced hypotension followed by bradycardia, the latter being also observed on ECG in anesthetized animals. CDC did not induce any atrial effect isolated from hypertensive rats. CONCLUSION: These data together demonstrate that the cardiac effect of CDC may be due to a non-toxic mechanism and depend on the NO/cGMP/PKG pathway to induce its negative inotropic effect.